2006
DOI: 10.1071/ah060516
|View full text |Cite
|
Sign up to set email alerts
|

Nursing morale: what does the literature reveal?

Abstract: There is increasing attention to nursing workforce issues such as recruitment, retention, turnover, workplace health and safety issues and their impact on quality patient care. A number of these problems have been linked to poor morale. While there has been a lack of consensus on the determinants of morale, it is clear that the outcomes of poor morale not only add considerable cost to the organisation but also impact negatively on patient care. This article provides a systematic overview of the literature surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…The importance of group interaction and its effect on the concept of morale suggest that the stability of the group's cohesion depend on morale (Daum, 1993). When supportive professional relationships with medical staff were present, nurses reported that their work was more meaningful and satisfying and that their professional knowledge and skills were used (Day et al, 2006). Nursing students in the study also presented a similar situation.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The importance of group interaction and its effect on the concept of morale suggest that the stability of the group's cohesion depend on morale (Daum, 1993). When supportive professional relationships with medical staff were present, nurses reported that their work was more meaningful and satisfying and that their professional knowledge and skills were used (Day et al, 2006). Nursing students in the study also presented a similar situation.…”
Section: Discussionsupporting
confidence: 54%
“…Nursing students in the study also presented a similar situation. On the basis of Orme's (1978) report, positive morale was seen as an attitude of confidence in the mind of the individual where they identified with a group, accepted group goals, and worked toward achieving them collectively (cited in Day et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…, 2006). Morale is a key indicator of absenteeism, commitment, turnover and productivity; however, to date, few studies have examined this issue for Australian nurses (Day et al. , 2006).…”
Section: Introductionmentioning
confidence: 99%